Comparison of two multiplex arrays in the diagnostics of allergy. Issue 1 (8th July 2019) - Bojcukova, Jana; Vlas, Tomas; Forstenlechner, Peter; Panzner, Petr
Abstract: The objective of this analysis was to compare the multiplex ImmunoCAP ISAC (Thermo Fisher Scientific, Sweden) and the multiplex Alex Allergy Explorer (Macro Array Diagnostics GmbH, Austria) platform on specific IgE to grass pollen (Phl p 1, Phl p 5), tree pollen (Bet v 1), house dust mites (Der p 1, Der p 2) and cat (Fel d 1) allergens in allergic patients. Our findings demonstrate a good correlation of presently used methods to detect serum sIgE. Multiplex testing of allergen‐specific IgE can be the method of choice for a prospective component‐resolved diagnosis of type I allergy, and the basis for the design and monitoring of a patient‐tailored specific therapy.